1994
DOI: 10.1149/1.2055041
|View full text |Cite
|
Sign up to set email alerts
|

Dual Intercalating Molten Electrolyte Batteries

Abstract: The reductive and oxidative intercalation of ions into graphite from room-temperature and low temperature molten salts is demonstrated. For this investigation, the molten salts use 1 -ethyl-3-methylimidazolium (EMI +) or 1,2-dimethyl-3-propylimidazolium (DMPI +) as the cation and AICI4, BF~, PF6, CF3SO~, or C6H5CO~ as the anion. In a two-electrode battery configuration, the molten salt electrolyte provides both the cation and anion which are intercalated into the graphite anode and cathode, respectively. A cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
231
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(238 citation statements)
references
References 1 publication
1
231
0
3
Order By: Relevance
“…31 With the addition of water, the prominent absorption feature around ∼3078 cm -1 spossibly the symmetric and antisymmetric stretch vibrational modes of HC (4) Figure 4c, the IR absorption spectra in this range are almost identical for both samples, suggesting the imidazolium cation separated from the anion and was surrounded by water molecules. The change in the 2800-3000 cm -1 range with increasing water content is relatively minor for both samples; the blue shift of ν SS CH 3 and ν FR CH 3 of the butyl chain was ∼10 cm -1 with increasing water content based on multipeak Gaussian fitting. 31 4 ] it is nearly intact even 48 h after the mixture was made (Figure 5b).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…31 With the addition of water, the prominent absorption feature around ∼3078 cm -1 spossibly the symmetric and antisymmetric stretch vibrational modes of HC (4) Figure 4c, the IR absorption spectra in this range are almost identical for both samples, suggesting the imidazolium cation separated from the anion and was surrounded by water molecules. The change in the 2800-3000 cm -1 range with increasing water content is relatively minor for both samples; the blue shift of ν SS CH 3 and ν FR CH 3 of the butyl chain was ∼10 cm -1 with increasing water content based on multipeak Gaussian fitting. 31 4 ] it is nearly intact even 48 h after the mixture was made (Figure 5b).…”
Section: Resultsmentioning
confidence: 88%
“…[1][2][3] Thus molecular design, synthesis, and characterization of RILs have been the focus of many recent scientific investigations. [4][5][6] However, one of the barriers in the application of RILs is the general lack of physical property data for these compounds toward fundamental understanding of the system.…”
Section: Introductionmentioning
confidence: 99%
“…This would be due to the electrochemical organic cation intercalation into the graphite layers [1,2] before the formation of a solid electrolyte interface (SEI) film on the graphite particles during the 1st charging. Recently, it has been reported that the graphite electrode indicated good charge-discharge characteristics by adding an additive such as vinylene carbonate [3] to the RTILs or using the RTILs such as…”
Section: Introductionmentioning
confidence: 99%
“…The reversible fluorination of graphite using the principle of dual ͑de͒intercalation of Li + at the anode and F − at the cathode opens the door to an interesting and potentially high-energy density variant on the Li-ion battery cell design. Other groups [6][7][8][9] have considered the advantages of a dual-ion intercalating battery, such as high cell voltage, using for example lithium cations and large polyatomic anions PF 6 − or ClO 4 − . These studies demonstrated successful cell operation, albeit with modest capacity and cycle life presumably due to the ͑de͒-intercalation of large polyatomic anions and poor anodic stability of the electrolyte solvent.…”
mentioning
confidence: 99%